Considering Culture and Conflict: A Novel Approach to Active Bystander Intervention - Kathryn C. Stephens; Tené Redman; Reneé Williams; Belinda Bandstra; Ripal Shah (Association of American Medical Colleges, 2023)
Introduction Workplace microaggressions are prevalent in clinical settings and contribute to poorer mental health outcomes, as well as to higher rates of burnout for physicians and students experiencing them. While bystander workshops customarily provide guidance on direct interventions to a general audience, the literature does not yet address workshops in an academic setting that consider the individual's motivations and behavior patterns. We implemented a psychologically informed approach to microaggression training to increase participants' understanding and willingness to undergo behavioral change. Methods We created a survey that included 10 distinct scenarios of discrimination in the clinical setting. Participants' willingness to intervene was assessed on a Likert scale prior to, then following, a 1-hour active bystander intervention workshop conducted virtually. The workshop outlined the role of culture and conflict management style in willingness to intervene. Four modes of intervention were outlined, including direct and indirect methods. Results A total of 78 medical students, graduate students, residents, and faculty members participated in the workshop. Of those, we compared 68 individuals' pre- and postworkshop responses to our questionnaire. We then focused on the 54 participants with no previous training in psychiatry or psychology. Utilizing a Wilcoxon signed rank test, we compared the average pre/post scores of willingness to intervene and found scores to have improved following workshop attendance (Z = −6.339, p < .001). Discussion Our findings suggest that a psychiatrically informed and culturally sensitive approach to active bystander intervention workshops may promote upstanding more effectively in academic medicine.